Chambers key-word dictionary (Edinburgh, 1998)
The book presents over 3.500 key words and phrases, and 4.000 definitions; full-sentence definitions show words in context; hundreds of synonyms and antonyms help with vocabulary-building
Keywords: english language - dictionaries